SENAM ASIK DAPAT MENURUNKAN NYERI MUSKULOSKELETAL PADA KELOMPOK WANITA TANI - Sumardiyono, Sumardiyono; Fajariani, Ratna; Chairunisa, Nabila Dian; Yasmine, Amalia; Avrilla, Syafina Nadya; Zakaria, Rais Athfal; Anugraeni, Devitasari; Mudrikah, Halimatul; Azzahra, Nirwana Putri; Kamil, Izzan; Daffa, Muhammad; Raihan, Raihan; Novrihaedi, Dziad (Poltekkes Kemenkes Bandung, 2024)
Work-related musculoskeletal pain is a serious occupational health problem worldwide. Farmers are one of the groups of people who are most at risk of developing this condition. To help reduce musculoskeletal pain, farmers can participate in a exercise program called